2018
DOI: 10.1016/j.jtho.2018.07.096
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis of Transcriptome and Epigenome Features of ASCL1–Positive Lung Adenocarcinomas

Abstract: These results suggest that ASCL1 defines a subgroup of lung adenocarcinoma with distinct molecular features by driving super-enhancer-mediated transcriptional programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Consistently, our genome‐wide analysis of SCLC cells revealed that TTF‐1 binding regions and TTF‐1‐regulated genes are associated with cellular differentiation and neural development. Of note, LADC that expresses ASCL1 shows neuroendocrine phenotype (Miyashita et al , ). Other reports indicate that LADC transforms into SCLC during the course of clinical treatments (Ferrer et al , ; Marcoux et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our genome‐wide analysis of SCLC cells revealed that TTF‐1 binding regions and TTF‐1‐regulated genes are associated with cellular differentiation and neural development. Of note, LADC that expresses ASCL1 shows neuroendocrine phenotype (Miyashita et al , ). Other reports indicate that LADC transforms into SCLC during the course of clinical treatments (Ferrer et al , ; Marcoux et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome and methylation profiles of lung cancer in IPF patients also remain to be elucidated. Recent studies have suggested that lung cancers of each histological subtype can be further subclassified based on gene expression and methylation patterns, which is related to different responses to cytotoxic agents, molecular targeted therapies, and immune checkpoint inhibitors [ 102 , 103 ]. Given that the mutation burden of lung cancer complicated with IPF is relatively high, as suggested by a recent report [ 62 ], immune checkpoint inhibitors might be beneficial.…”
Section: Clinical Implications and Future Perspectivesmentioning
confidence: 99%
“…Integrated analysis of methylation and gene expression for diagnosis, treatment, or prognosis has been reported in breast cancer, lung cancer, thyroid cancer, and hepatocellular carcinoma, head and neck squamous cell carcinoma, and polycystic ovary syndrome. 11 , 12 , 13 , 14 , 15 , 16 Although CC screening programs are now carried out worldwide, many women are still diagnosed with advanced CC which the overall prognosis remains poor. To date, only a limited number of reports about biomarkers were identified in CC by multi‐omics integrated analysis.…”
Section: Introductionmentioning
confidence: 99%